FORMATION OF PROTECTIVE MECHANISMS IN THE PERSONALITY OF A TEENAGER - Omonovich, Khimmataliev Dustnazar; Ergashevna, Burieva Kibrio (Universitas Negeri Malang, 2024)
The purpose of this study is the formation of protective mechanisms in the personality in adolescence. In this study, an observation method was used - with the help of this method, the daily educational activities of students were systematically monitored, and the information collected was recorded in a special diary as well as psychological tests: the methodology for determining the protective mechanism of personality (developed by the cheat),а questionnaire to determine the nature of subjective local control (developed by S.R.Panteleev, V.V.Stolin), determination of the nature of personality aggressiveness by the Bass-Darky method. This study was conducted to obtain accurate data, the data collected on the basis of the studied literature and the results of the conducted research contributed to the identification of protective mechanisms in the personality of a teenager. Also, the generalization and systematization of sources obtained from experimental work on personal protection mechanisms contributes to the improvement of the younger generation, who are brought up in educational institutions, as a necessary member of society. Based on this, teenagers can be effective tools in solving various problematic situations, the ability to rationally get out of them. The findings can be widely used in their work by practical psychologists, parents and employees of an educational institution. the relationship between the two variables. The results showed that the occurrence of aggressive states in adolescence may be associated with emotional states in them. Because if we look at the situation based on the psychological characteristics of adolescence, this period is the most dynamic in personal maturation, saturated with emotions and determined by the power of aggression. Therefore, it is necessary to form emotional management skills in the personality of a teenager. And this, in turn, will help to avoid various aggressive situations that arise in the personality of a teenager. Keywords: the personality in adolescence, protective mechanisms, the formation, problematic situations